2014
DOI: 10.1002/anie.201405251
|View full text |Cite
|
Sign up to set email alerts
|

Interrupted Imino‐Nazarov Cyclization of 1‐Aminopentadienyl Cation and Related Cascade Process

Abstract: Facile 4π conrotatory imino-Nazarov cyclization of a 1-aminopentadienyl cation generated from condensation an aldehyde and secondary aniline in the presence of a catalytic amount of a Lewis acid has been developed. Silver(I)-catalyzed intramolecular arene trapping of the resulting cyclic oxyallyl cation leads to formation of tricyclic indoline-fused cyclopentanone. The use of lanthanide salts allows transformation after the initial trapping to afford tetrahydroquinoline-fused cyclopentenone in a concise manner. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…On the other hand, it is reported that 59 % of U.S. FDA approved small molecule drugs contain nitrogen heterocycles . Based on these, our group has described a cascade Lewis‐acid catalyzed reaction of Perlin aldehyde‐derived dienals and secondary anilines, involving interrupted imino‐Nazarov reaction as the key step, which results in the formation of fused indoline and tetrahydroquinoline products . However, toxic reagents were applied to synthesize the starting material dienals in three steps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is reported that 59 % of U.S. FDA approved small molecule drugs contain nitrogen heterocycles . Based on these, our group has described a cascade Lewis‐acid catalyzed reaction of Perlin aldehyde‐derived dienals and secondary anilines, involving interrupted imino‐Nazarov reaction as the key step, which results in the formation of fused indoline and tetrahydroquinoline products . However, toxic reagents were applied to synthesize the starting material dienals in three steps.…”
Section: Methodsmentioning
confidence: 99%
“…The key feature of this protocol is the practical use of readily available biomass‐derived glucal as the starting material. This precludes the use of a highly toxic mercury reagent in the lengthy preparation of the corresponding dienal, thus rendering the overall process far more step‐economical and environment‐friendly.…”
Section: Methodsmentioning
confidence: 99%
“…An efficient cyclization of the imines generated in situ by condensation of aldehyde 181 with secondary anilines in the presence of silver salts has been studied (Scheme ) . Anhydrous conditions are required for an interrupted reaction to proceed, otherwise there is proton elimination leading to aminocyclopentenone 186 .…”
Section: Interrupted Nazarov‐type Reactionmentioning
confidence: 99%
“…12 In particular, the interrupted Nazarov cyclization has been developed extensively for rapid access to complex functionalized cyclopentenones. 13 Although the Nazarov cyclization of divinyl ketones has been studied thoroughly, examples of Nazarov cyclization based on 1,4-pentadien-3-ols are relatively scarce. 14 In the limited examples, 1,4-pentadien-3-ols were treated with a Brønsted or a Lewis acid to form pentadienyl cations, which underwent 4π-electrocylic ring closure to afford the cyclopentadiene products.…”
mentioning
confidence: 99%